On the Supersymmetry of the Klein-Gordon Oscillator - Junker, Georg (Symmetry, 2021)
The three-dimensional Klein-Gordon oscillator exhibits an algebraic structure known from supersymmetric quantum mechanics. The supersymmetry is unbroken with a vanishing Witten index, and it is utilized to derive the spectral properties of the Klein-Gordon oscillator, which is closely related to that of the nonrelativistic harmonic oscillator in three dimensions. Supersymmetry also enables us to derive a closed-form expression for the energy-dependent Green's function.
CRIS-Team WoS Importer:2021-06-04